AKTIVITAS ANTIBAKTERI GRAM POSITIF Bacillus cereus DARI EKSTRAK DAUN MANGROVE (Sonneratia alba) MUDA - Ramadhani, Anissa El; Sari, Noor Ira; Sidauruk, Santhy Wisuda (Marinade, 2022)
Sonneratia alba is one of the type of mangrove that has been used by people in coastal areas. S. alba leaves are known to have bioactive compounds that have potential as antibacterial. B. cereus is a pathogenic bacteria that can cause food spoilage, especially in fishery products, so its growth must to be inhibited using natural antibacterial such as S. alba leaves. This study aims to qualitatively determine the components of bioactive compounds in S. alba leaf extract and the antibacterial activitty of S. alba leaf extract. This study consisted of exctracting the leaves of S. alba using aquadest as a solvent with a\ration of 1:30, phytochemical test and analysis of antibacterial activity using the well difussion method and the dilution method at different concentration of extract 100%, 50%, 25% and 12,5%. The leaf extract of S. alba had a yield 11,33% and contains bioactive compounds such as alkaloids, flavonoids, triteroenoids, saponins and tannins. S. alba leaft extract can inhibit the growth of B. cereus bacteria. The diameter of the inhibition of S. alba leaf exctract against B. cereus bacteria with the highest concentration of 100% was 13,43±0.30 mm. S. alba leaf extract is bacteriostatic. Keywords: antibacterial, bioactive, B. cereus, extraction, S. alba.